A Sociolinguistic Study on the Development of Grammar System of Treatment Expression - Akira Yonemoto (Journal La Sociale, 2020)
Analysis of the language in which honorific expressions are developed has revealed various findings. The social and cultural background can be considered by analyzing the history of the honorifics, etc., but the honorifics are often used in colloquial language. Is also an issue of this research. Since honorifics reflect not only their practical aspects but also society, culture, and ideas, it is one clue to know from the history and usage of honorifics, and there is room for sociolinguistic analysis and consideration. Is an area where there are still many.